FACTORS AFFECTING PLAGIARISM AMONG POSTGRADUATE RESEARCH SCHOLARS - Rabia Aslam; Dr. Munira Nasreen Ansari (International Journal of Contemporary Issues in Social Sciences, 2024)
Plagiarism is the unethical use of another’s work. The term today is highly used in the context of research work. This paper aims to explore the possible factors that lead to plagiarism through the perception of postgraduate research students. The study evaluates the cases of postgraduate research students using survey questionnaires and discussions, both techniques were used to collect data. The population selected was UOK postgraduate student session 2019-2023. The total population was 589 out of which 156 were the targeted sample. The sampling technique used to reach the population was snowball sampling. The findings revealed that research ethics plays a vital role in fostering upcoming researchers toward ethical contributions to society. Insufficient knowledge of plagiarism, technology, and institutional policies are the issues of postgraduate research scholars. The study is entirely based on the practical usage of literary material in post-graduate studies, the paper should be of interest to academicians, research supervisors, and members of the curriculum development committee. The study is the only evaluation of postgraduate research students of UOK-Pakistan in terms of their knowledge and approaches towards research. The findings will aid in designing educational policies and re-designing current practices of research students.